On the Generalized Deteriorated Positive Semi-Definite and Skew-Hermitian Splitting Preconditioner (Journal of Computational Mathematics, 2018)
For nonsymmetric saddle point problems, Huang et al. in [Numer. Algor. 75 (2017),pp. 1161-1191] established a generalized variant of the deteriorated positive semi-definiteand skew-Hermitian splitting (GVDPSS) preconditioner to expedite the convergence speedof the Krylov subspace iteration methods like the GMRES method. In this paper, somenew convergence properties as well as some new numerical results are presented to validatethe theoretical results.